2018
DOI: 10.1590/0034-7167-2017-0444
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Brief Intervention for the use of alcohol and other drugs

Abstract: Objective: to identify the lifetime use of alcohol and other drugs among users of the Family Health Strategy and apply Brief Intervention to problems related to the use of these substances. Method: a descriptive cross-sectional study where 1,031 users of the Family Health Strategy of the city of Rio de Janeiro answered a form with socio-demographic information and the Alcohol, Smoking and Substance Involvement Screening Test. Statistical analysis with simple frequency distribution was performed. Results: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
2
0
4
Order By: Relevance
“…Although frequent use of hypnotics was identified, a scientific study (Abreu et al, 2018) also found a predominance in the use of marijuana, cocaine, and crack (4.2%), as was evidenced among the participants in this investigation.…”
Section: Discussionsupporting
confidence: 63%
“…Although frequent use of hypnotics was identified, a scientific study (Abreu et al, 2018) also found a predominance in the use of marijuana, cocaine, and crack (4.2%), as was evidenced among the participants in this investigation.…”
Section: Discussionsupporting
confidence: 63%
“…Among adults utilising a community‐based health programme in a vulnerable socio‐economic community in Rio de Janeiro state in 2013/2014 ( n = 1031), 8.4% had a lifetime history of cannabis use; 1.2% were considered to have a moderate use risk evaluated by the ASSIST [85]; furthermore, approximately 2% of care‐seeking individuals in the general health unit ( n = 1489) of the same community reported cannabis use in the prior 3 months [86]. Among adult male inpatients ( n = 209) of a psychiatric hospital in Maringá (Paraná) in 2016, 73% reported lifetime use of cannabis, and 16% and 33% of the sample had moderate and high risk related to cannabis use (ASSIST‐based), respectively [87].…”
Section: Resultsmentioning
confidence: 99%
“…Assim, podemos destacara como estratégia de intervenção, a utilização de técnicas terapêuticas sucintas e de pequena duração, a exemplo da "Intervenção Breve", uma técnica terapêutica direcionada a mudança de conduta, na busca por redução de danos, ajudando os usuários a perceber que tal uso lhes causam riscos, tornando-se uma motivação para que reduzam ou deixem de consumir tais substâncias. (22) Desse modo, é imprescindível garantir estratégias para o acolhimento aos usuários e que estes se sintam confiantes e estabeleçam vínculos com os profissionais de saúde e os serviços, de modo a viabilizar um cuidado que vá ao encontro das reais necessidades de usuários e famílias. Como outras estratégias destacamos o acolhimento, o PTS, a referência técnica, a visita domiciliar e as reuniões de equipe como importantes ferramentas para a produção do cuidado aos usuários, práticas que requer um comprometimento por parte de toda equipe.…”
Section: Discussionunclassified